Managing Teachers' Job Attitudes: The Potential Benefits of Being a Happy and Emotional Intelligent Teacher - Peláez-Fernández, María Angeles; Mérida-López, Sergio; Sánchez-Álvarez, Nicolás; Extremera, Natalio (Frontiers in Psychology, 2021)
According to Fredrickson’s broaden-and-build theory of positive emotions (Vacharkulksemsuk and Fredrickson, 2013), the frequency of positive emotions is associated with the development of positive attitudes, cognitions, and behaviors in organizational contexts. However, positive and negative attitudes at work might also be influenced by different personal and job resources. While emotional intelligence has been significantly associated with positive job attitudes and personal wellbeing, no studies have yet examined the joint role of teacher happiness and emotional intelligence on key teacher job attitudes. The present study assesses whether emotional intelligence interacts with levels of teacher happiness to jointly explain important teacher job attitudes (i.e., job satisfaction and turnover intention). A total sample of 685 teaching professionals (431 female) filled out a battery of scales including subjective happiness, emotional intelligence, job satisfaction, and turnover intention. Our results revealed that subjective happiness was significantly associated with higher job satisfaction and lower turnover intention. Likewise, emotional intelligence was positively related to happiness and job satisfaction, and negatively to turnover intention. Finally, interaction analysis showed the main effects of happiness and emotional intelligence in explaining teacher job attitudes. Beyond the main effects, the interaction effects of happiness and emotional intelligence were significant in predicting all teachers’ job attitude indicators, even controlling for the effects of their sociodemographic variables. This work expands our knowledge about the role of teachers’ positive emotions in the development of positive work attitudes and also suggests the inclusion of emotional skills in future teacher preparation programs as resources to facilitate work-related wellbeing.